Instruction of Metacognitive Strategies to Enhance Students’ Listening Comprehension - Krishnan, Latha K.; Kepol, Napisah (Asian Journal of Assessment in Teaching and Learning, 2013)
The listening skill has been reported as a neglected skill in the ESL classroom. The lack of attention to this particular skill has been linked to ESL students’ poor performance in authentic communication and examinations. The study reported in this paper examined the effectiveness of explicit instruction on metacognitive strategies in enhancing students’ listening comprehension skills. A quasi-experimental research design which involved pretest-posttest control and experimental groups was used. A semi-structured questionnaire was also distributed to gather information about the students’ perceptions in using metacognitive strategies to monitor their listening comprehension. 90 Upper Sixth Form students in a Malaysian school were selected to participate in this study and they were divided into two experimental groups and one control group. The treatment in the form of explicit instruction and modeling of metacognitive strategies in listening comprehension was given to the experimental groups while the control group was taught using the conventional non-metacognitive product-based method. The pretest and posttest results were analysed using the paired t-test and data from the questionnaire were analysed using frequency counts and thematic coding. The findings showed that there was a significant difference in the scores obtained by students treated with explicit instruction of metacognitive strategies compared to the conventional method. Data from the semi-structured questionnaire displayed students’ positive responses in using metacognitive strategies to monitor their listening comprehension. These findings provide support for the instruction of metacognitive strategies to be included as a beneficial pedagogical method to enhance students’ listening comprehension in the ESL classroom. Explicit instruction, metacognitive strategies, listening skill.